Pengaruh Harga Jual, Transportasi dan Biaya Terhadap Pendapatan Petani Kayu Manis (Cinnamomum Verum ) di Kecamatan Loksado - Rizki, Muhammad; Sopiana, Yunita (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
The income of cinnamon farmers can be influenced by various factors, both internal and external factors. This study uses internal factors such as the selling price, distance, and cost as variables. This study aims to determine the influence of variable selling prices, spreads, and expenses on the income of cinnamon farmers in the Loksado District. The data source used in this study was primary data in interviews with a sample of 20 respondents. The analysis tool used is multiple linear regression with income as the dependent variable and three independent variables, namely selling price (Rp), distance (Km), and cost (Rp). Multiple linear regression will test the influence simultaneously (f test) and partially (t-test) through eviws10 software. The results of this study showed that variable free selling price, distance, and cost that is influential simulant or together and partially or each variable affects the income of cinnamon farmers; in this study, dependent variables (gain) can be explained by independent variables (capital, labor, and working hours) of 100%. The test results and analysis show that free variables such as selling price and cost have a significant partial effect and variable distances have no considerable impact. Then the most dominant variable affecting the income of cinnamon farmers is the variable selling price. Based on the study results, the conclusion that can be applied to increase income is to manage the selling price as best as possible regularly because the higher the selling price, the greater the profit for cinnamon farmers. But if the selling price is too high, the consumer will be reduced. Therefore the price must be adjusted to the demand. Then use transportation so that the distance traveled is not too far, and use the cost by the needs of cinnamon tree land.